RANCANG BANGUN APLIKASI E-LEARNING BERBASIS ANDROID UNTUK PEMBELAJARAN ENGLISH FOR TOURISM AND HOSPITALITY - Nurmi Hidayasari; Fanalisa Elfa; Diah Paramita Sari (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
There is a wide range of material that must be understood and mastered by students in studying English grammar so that not only the teaching material must be in accordance with student needs, especially vocational students who have learning needs for English For Tourism And Hospitality, but the media used must also be more complete and interesting. However, from the results of the survey conducted, the teaching materials and educational applications offered in the Android application on Playstore do not meet learning needs, especially in English For Tourism And Hospitality. This research aims to develop an interesting Android-based learning or e-Learning application using the Extreme Programming (XP) development method. To ensure that the functions of the application being created work as expected, Black Box testing will be carried out. The results obtained from designing an Android-based e-Learning application for For Tourism and Hospitality material using the XP method were successful and the application can be used according to the design. There are no menus in the application that fail to process and execute according to function.